Understanding student engagement: an examination of the moderation effect of professional teachers' competence - Maryani, Ika; Irsalinda, Nursyiva; Jaya, Patria Handung; Sukma, Hanum Hanifa; Raman, Arumugam (Journal of Education and Learning (EduLearn), 2025)
Due to low levels of student engagement during the COVID-19 pandemic, elementary school students suffered significant learning losses, which served as the driving force behind this research. Teachers should be the key to solving problems. This research aims to measure how much influence the competence of professional elementary school teachers has on student engagement in Indonesia. This research uses a quantitative approach with a correlational design and survey method. Data collection was carried out through teacher professional competency and student involvement questionnaires, with data sources coming from elementary school teachers and students in the western, eastern, and central regions of Indonesia. Samples were taken using the cluster random sampling technique. Quantitative data analysis was used with descriptive statistical stages, correlation analysis, regression analysis, and comparative analysis. The results of the hypothesis test also show that professional competence in the aspect of understanding content and understanding the curriculum has a significant influence on student engagement, while in the aspect of understanding student character, it does not have a significant influence. These results make an important contribution to teachers' ongoing professional development. Aspects of content development and curriculum development are recommended as priorities for self-development.